2009
DOI: 10.1016/j.virol.2008.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with virus-like particles protects mice from lethal infection of Rift Valley Fever Virus

Abstract: Rift Valley Fever virus (RVFV) regularly accounts for severe and often lethal outbreaks among livestock and humans in Africa. Safe and effective veterinarian and human vaccines are highly needed. We present evidence that administration of RVF virus-like particles (VLPs) induces protective immunity in mice. In an accompanying paper, (Habjan, M., Penski, N., Wagner, V., Spiegel, M., Overby, A.K., Kochs, G., Huiskonen, J., Weber, F., 2009. Efficient production of Rift Valley fever virus-like particles: the antivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 281 publications
(440 reference statements)
3
67
1
1
Order By: Relevance
“…We and others have previously reported efficient VLP production systems and VLPs comprising only the Gn and Gc proteins are highly effective vaccine candidates (20,29,31,32,35,38). Mandell et al demonstrated that including the N protein in VLPs improves vaccine efficacy (31), which could be due to stabilization of the particle and/or to partial protective efficacy mediated by the N protein alone (11).…”
Section: Discussionmentioning
confidence: 98%
“…We and others have previously reported efficient VLP production systems and VLPs comprising only the Gn and Gc proteins are highly effective vaccine candidates (20,29,31,32,35,38). Mandell et al demonstrated that including the N protein in VLPs improves vaccine efficacy (31), which could be due to stabilization of the particle and/or to partial protective efficacy mediated by the N protein alone (11).…”
Section: Discussionmentioning
confidence: 98%
“…To address this concern, we developed and tested two rVACV vaccines for RVF for use in animals. Other vaccines in development for RVF include attenuated RVFV strains with deletions in the NSs gene (25), DNA, and subunit (27)(28)(29)(30). Recombinant poxvirus vaccines have been previously developed using the lumpy skin disease virus or the WR strain of VACV as vectors (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Inactivated RVFV vaccines, such as TGI-GSD-200, are safe for use in pregnant and young animals but are less immunogenic (27). Similarly, subunit and DNA vaccines are also safe but poorly immunogenic, requiring multiple immunizations (27)(28)(29). Another significant advantage of the rVACVs is their heat stability, thus eliminating the need for Initial vaccination was administered by scarification on day 0, and the intramuscular booster inoculation was given on day 28.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of recently developed candidate vaccines include DNA-vectored (2,24,27), virus-like particle (VLP) (11,29,31), replicon particle (RRP) (23), and live attenuated (5, 13) vaccines. VLP candidates show promise and remarkable safety but generally require adjuvant and/or multiple immunizations for complete protection.…”
mentioning
confidence: 99%